2015
DOI: 10.18632/oncotarget.3453
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumor infiltrating Natural Killer cell subset

Abstract: The presence of tumor-infiltrating Natural Killer (NK) within a tumor bed may be indicative of an ongoing immune response toward the tumor. However, many studies have shown that an intense NK infiltration, is associated with advanced disease and may even facilitate cancer development. The exact role of the tumor infiltrating NK cells and the correlation between their presence and poor prognosis remains unclear. Interestingly, during pregnancy high numbers of a specific NK subset, CD56brightCD16dim, are accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 17 publications
8
79
0
Order By: Relevance
“…Interestingly, this also was demonstrated in PF from a patient with gastric cancer (60). One might hypothesize that the accumulation of CD56 bright NK cells in the peritoneum is the consequence of obstruction of the peritoneal lymphatic circulation, because this subpopulation is characteristic of secondary lymphoid organs.…”
Section: Cd56 Bright Nk Cells In Tissuesmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, this also was demonstrated in PF from a patient with gastric cancer (60). One might hypothesize that the accumulation of CD56 bright NK cells in the peritoneum is the consequence of obstruction of the peritoneal lymphatic circulation, because this subpopulation is characteristic of secondary lymphoid organs.…”
Section: Cd56 Bright Nk Cells In Tissuesmentioning
confidence: 70%
“…However, the lack of information on the composition of NK cell subsets in the peritoneum of healthy donors makes a conclusion difficult. Nevertheless, it should be noted that PF from a patient with pancreatic cancer did not exhibit such an accumulation of CD56 bright cells; the CD56 dim subset was the major population (60). This discrepancy between cancer types may indicate that tumor-related factors are involved in the modulation of CD56 expression.…”
Section: Cd56 Bright Nk Cells In Tissuesmentioning
confidence: 91%
See 1 more Smart Citation
“…Expression levels were normalized to the vehicle control. detected in patients with non-small cell lung cancer, breast tumors, and colon tumors ( 33,34 ). The presence of VEGFAproducing NK cells is associated with a poor prognosis, showing that NK-cell-derived VEGFA plays a part in human disease.…”
Section: Y694mentioning
confidence: 99%
“…While the biological and clinical significance of their presence in early pregnancy is still under investigation, there are supporting evidences for both inhibitory and activating features, either in inhibition of anti-fetal immune response or in promotion of angiogenesis to support fetus implantation [26][32]. Recently it was shown that there was a significant enrichment of decidual-like NK cells within tumor infiltrating NK cell population which express pro-angiogenic factors and contribute to the tumor development [33]. Here we show that PILRα as a NK ligand, also activates dNK function by promoting killing and IFNγ secretion.…”
Section: Discussionmentioning
confidence: 99%